The ultrastructure of the mullet Mugil curema Valenciennes (Teleostei, Mugilidae) spermatozoa - Eiras-Stofella,Daura Regina (1993)
The structure of the spermatozoon of Mugil curema Valenciennes, 1836 was studied using scanning and transmission electron microscopy. The spermatic head is rounded and formed by the nucleus containing granular chromatin, firmly packed resulting in a mass extremely electron dense. The acrossome is absent. The midpiece is characterized by the presence of two centrioles, a plasmatic canal, very few vesicles, and several mitochondria (9-10) with aproximately 0.50µm in diameter. The head and the midpiece are aproximately 1.56µm in diameter. The flagellum conforms to the 9 + 0 flagellar pattern near the transition region in its midpiece and is 9 + 2 from there on up to the distal region of the axoneme. The electron density in the A tubules 1, 2, 5 and 6 shows the asymetry of this spermatozoa. Its spermatic cell differs ultrastructuraly from those of other Mugilidae species mainly because it has the highest number of mitochondria.